Evaluation of the Industrial Work Practice Implementation Program (Prakerin) Using the CIPP Model (Context, Input, Process, Product) in the Motorcycle Engineering an Business Department at Vocational High School (SMK) Negeri 1 Bangsri Jepara - Hasanuddin, Hasanuddin; Yulianto, Arief; Widiyanto, Widiyanto (Educational Management, 2022)
The background of this research is the lack of absorption of graduates from SMK Negeri 1 Bangsri Jepara, Department of Motorcycle Engineering and Business, who work not according to their majors. The research method used is a qualitative method and the evaluation model used in this study is the CIPP evaluation model. Data collection techniques by means of in-depth interviews, observations and documentation studies. And data analysis techniques with data collection, data reduction, data presentation, verification and confirmation of conclusions.Research shows that context evaluation is appropriate, as evidenced by the learning process in schools that has been fulfilled in the implementation of direct practice in the world of work. Input evaluation is appropriate as evidenced by the planning, implementation and evaluation of Industrial Work Practices. Process evaluation found that students were able to carry out the Industrial Work Practice program well, but the monitoring activities of the supervising teacher were not optimal. Product evaluation has been well demonstrated by changes in the skills of competent students after carrying out the Industrial Work Practice program.The results of the study can be concluded that the Evaluation of the Industrial Work Practice Implementation Program using the CIPP model in the Motorcycle Engineering and Business Department at SMK Negeri 1 Bangsri Jepara through the stages of planning, implementation, evaluation and follow-up can provide information for improving the quality of Education in SMK.